2013
DOI: 10.1056/nejmoa1303342
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium Respimat Inhaler and the Risk of Death in COPD

Abstract: Tiotropium Respimat at a dose of 5 μg or 2.5 μg had a safety profile and exacerbation efficacy similar to those of tiotropium HandiHaler at a dose of 18 μg in patients with COPD. (Funded by Boehringer Ingelheim; TIOSPIR ClinicalTrials.gov number, NCT01126437.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
2
17

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(256 citation statements)
references
References 21 publications
10
227
2
17
Order By: Relevance
“…Parameters were similar between treatment arms [same molecule: tiotropium; same dosing frequency: once daily (OD)], except for the inhaler device and the Similar results were also found in the Japanese study population [11]. Finally, the safety profile and exacerbation efficacy of tiotropium Respimat ® 5 mg or 2.5 mg OD were found similar to those of tiotropium HandiHaler ® at 18 mg OD in a randomised controlled study (TIOSPIR), in which more than 17.000 patients were enrolled and followed during a period of 2.3 years on average [13].…”
Section: Respimat ® Vs Handihaler ®supporting
confidence: 72%
See 1 more Smart Citation
“…Parameters were similar between treatment arms [same molecule: tiotropium; same dosing frequency: once daily (OD)], except for the inhaler device and the Similar results were also found in the Japanese study population [11]. Finally, the safety profile and exacerbation efficacy of tiotropium Respimat ® 5 mg or 2.5 mg OD were found similar to those of tiotropium HandiHaler ® at 18 mg OD in a randomised controlled study (TIOSPIR), in which more than 17.000 patients were enrolled and followed during a period of 2.3 years on average [13].…”
Section: Respimat ® Vs Handihaler ®supporting
confidence: 72%
“…The improved therapeutic ratio is probably explained by the low velocity of the aerosol cloud, that enables a high lung deposition and high efficiency of the new device [44]. The prospective TIOSPIR study was specifically set up to compare the long-term safety of tiotropium delivered via Respimat ® vs. HandiHaler ® [13] in a direct way because concerns had arisen from metaanalyses and pharmaco-epidemiological data [45]. In essence, a numerical increase in all-cause mortality had been seen in pooled analyses of registration studies of tiotropium Respimat ® compared to placebo, which was in contrast to the much larger tiotropium HandiHaler ® database.…”
Section: Discussionmentioning
confidence: 99%
“…Tachycardia and atrial fibrillation have been reported and should be used with caution especially among patients with COPD as those patients are older with often-associated comorbidities. However, a recent meta-analysis does not confirm an increased risk of cardiovascular events [43].…”
Section: Anticholinergic/antimuscarinic Medicationsmentioning
confidence: 94%
“…Число летальных исходов и тяжелых ССО было сходным во всех 3 группах [30]. Продемонстрировано, что новая форма доставки меньшей дозы тиотропия обладает хорошим профилем безопасности.…”
Section: терапевтический архив 3 2016unclassified